Philogelos 23; 130 and the Meaning of οὐ λούει - Zueva, Daria; Zeltchenko, Vsevolod (Hyperboreus, 2024)
In two almost identical jokes from Philogelos (23; 130), a σχολαστικός (or a “Sidonian sophist”), on arriving at a bathhouse at its very opening, when no one else is in it, says: “As far as I can see, οὐ λούει”. According to Andreas Thierfelder, whose interpretation has prevailed in recent scholarship, the technical expression οὐ λούει (τὸ βαλανεῖον) means “the bath does not work”. With this understanding, however, the joke loses any salt: for even if the entrance doors are open, the sight of an empty bathhouse might naturally lead a visitor to think that it is not functioning for some reason. The authors deal with examples of the idiom (τὸ βαλανεῖον) λούει / balineum lavat meaning free access to the baths, which epigraphists and papyrologists have discussed more than once. As the closest parallel, a passage from the historian Olympiodorus (28 Müller [FHG IV 64] = Phot. Bibl. 80. 60b) is ﬁrst invoked, describing the initiation procedure to which newcomers were subjected in fourth- and ﬁfth-century Athenian schools. In endeavoring to prevent the novice from entering the deliberately locked bath, students shout, “Στᾶ, στᾶ, οὐ λούει”: as a parallel passage from Gregory Nazianzinus (Orat. 43. 16. 5) shows, this does not imply “the bath is not in operation”, but “there is no access”, “the bath is occupied”. Thus, the σχολαστικός, applying perverse logic, concludes that the visitors are not allowed into the bath because same “special event” is taking place there: in a completely empty bathhouse, these words sound absurd, which seems to restore the punchline to the joke.